Around Langlands correspondences - International Conference on Around Langlands Correspondences (Orsay, France 17-20 June, 2015); Brumley, Farrell; Gomez Aparicio, Maria Paula; Minguez, Alberto (Providence : American Mathematical Society, 2017)
This volume contains the proceedings of the international conference ``Around Langlands Correspondences'', held from June 17-20, 2015, at Universite Paris Sud in Orsay, France.The Langlands correspondence (nowadays called the usual Langlands correspondence), conjectured by Robert Langlands in the late 1960s and early 1970s, has recently seen some new mysterious generalizations: the modular Langlands correspondence, the $p$-adic Langlands correspondence, and the geometric Langlands correspondence, the last of which seems to share deep connections with the Baum-Connes conjecture.The aim of this volume is to present, through a mix of research and expository articles, some of the fascinating new directions in number theory and representation theory arising from recent developments in the Langlands program. Special emphasis is placed on nonclassical versions of the conjectural Langlands correspondences, where the underlying field is no longer the complex numbers.
Includes bibliographical references.
Keywords: Algebraic number theory -- Congresses; Galois theory -- Congresses